Analisis Reinkarnasi dalam Anime Fullmetal Alcemist Karya Hiromu Arakawa - Muhamad Alfian; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the relationship between human transmutation in the full metal alchemist film and the concept of reincarnation in Buddhism and to explain the meaning of transmutation and reincarnation. The method used in compiling this research is qualitative using two methods, namely the concept of reincarnation itself and Roland Barthes' semiotic theory. As reincarnation in Buddhism says that reincarnation is the process of transforming the soul into a new body, in alchemy it is said that a material can only be transformed into matter with the same properties and elements as the original material. In other words, if the alchemist aims to transmute humans or bring them back to life, what can be revived is only to return their souls and move to other bodies that are fellow humans. If the concept of reincarnation in general is an opportunity as penance and a field of charity. In contrast to reincarnation in full metal films, alchemists are the result of experiments to revive dead humans, using alchemists with the principle of